Studi Pengolahan Tepung Aren Dari Batang Arena Arenga Pinata Marr - Ton, Semris Novenri Marsantri; Halik , Abdul; Laga, Suriana (Fakultas Pertanian Universitas Bosowa, 2025)
The starch content in the larger aren tree trunks can produce an average aren starch ranging from 74.60% - 88.96% in the small aren trunks can produce aren starch ranging from 60.77% - 70.94% in the trunk section. Arenga flour is flour made from aren tree trunk starch, this aren flour is a semi-finished product and has a smooth nature so that it is used as a raw material for various traditional foods. This study aims to determine the effect of the duration of aren starch sedimentation on the water content, crude fiber, and organoleptic tests (color, aroma, and texture) of aren flour. The treatment of this study was the duration of aren starch sedimentation of 22 hours, 24 hours, 26 hours and 28 hours. Data analysis using Completely Randomized Design (CRD), and three replications. Data from the analysis of diversity with the Advanced Test (LSD). The parameters observed in this study consisted of water content tests, crude fiber tests and organoleptic tests on the color, aroma and texture of aren flour. Based on the results of the study, it was concluded that the treatment of the duration of sedimentation of palm starch had a significant effect on the water content and crude fiber of palm flour, but had a very significant effect on the color, aroma and texture of palm flour. The best treatment was obtained at a sedimentation time of palm starch of 28 hours in terms of water content of 8.01%, crude fiber 0.09%, color 4.32, aroma 4.22, and texture 4.38 of palm flour. It is recommended for further researchers to be able to analyze the yield and storage time of palm flour and analyze the fat, carbohydrate, and amylose content of palm flour. Kandungan pati pada batang pohon aren yang lebih besar dapat menghasilkan pati aren rata-rata berkisar antara 74,60% - 88,96% pada batang aren yang beukuran kecil dapat menghasilkan pati aren berkisar antara 60,77% - 70,94% pada bagian batang. Tepung aren adalah tepung yang terbuat dari pati batang pohon aren, tepung aren ini adalah produk stengah jadi dan memiliki sifat yang halus sehingga digunakan sebagai bahan baku berbagai macam makan tradisional. Penelitian ini bertujuan untuk mengetahui pengaruh lama pengendapan pati aren terhadap kadar air, serat kasar, dan uji organoleptik (warna, aroma, dan tekstur) tepung aren. Perlakuan penelitian ini yaitu lama pengendapan pati aren 22 jam, 24 jam, 26 jam dan 28 jam. Analisis data dengan menggunakan Rancang Acak Lengkap (RAL), dan tiga kali ulangan. Data hasil analisis keragaman dengan uji Lanjut (BNT). Parameter yang diamati pada penelitian ini terdiri dari uji kadar air, uji serat kasar dan uji organoleptik terhadap warana, aroma dan tekstur tepung aren. Berdasarkan hasil penelitian disimpulkan perlakuan lama pengendapan pati aren berpengaruh nyata terhadap kadar air dan serat kasar tepung aren, tetapi berpengaruh sangat nyata terhadap warna, aroma dan tekstur tepung aren. Perlakuan terbaik diperoleh pada lama pengendapan pati aren 28 jam ditinjau dari kadar air 8,01%, serat kasar 0,09%, warna 4,32, aroma 4,22, dan tekstur 4,38 tepung aren. Disarankan bagi peneliti selanjutnya untuk dapat menganalisis terhadap rendemen dan lama waktu penyimpanan tepung aren dan menganalisis kadar lemak, karbohidrat, dan kadar amilosa pada tepung aren.